The Influence of Social Media on Athletes’ Mental Health: A Bibliometric Analysis - Humaira Azzahra Putri Mulyana; Adang Suherman; Jajat Jajat; Kuston Sultoni; Fendi Ferdiana (Universitas Negeri Semarang, 2026)
This study aims to examine research trends related to the influence of social media on athletes’ mental health using a bibliometric analysis approach. A bibliometric trend analysis was conducted using data retrieved from the Scopus database. A total of 261 documents published between 2014 and 2025 were analyzed with VOSviewer to identify publication growth, author productivity, geographical distribution, collaboration networks, and keyword co-occurrence patterns. The results reveal a substantial increase in research output over the past decade, indicating growing academic interest in this topic. Key themes frequently addressed include mental health, fan engagement, self-presentation, anxiety, and psychological support for athletes. Research contributions are predominantly led by developed countries such as the United States, the United Kingdom, and Australia, highlighting strong international collaboration, while developing regions remain underrepresented. Keyword analysis demonstrates the dual role of social media, functioning both as a source of psychological pressure through criticism and social comparison, and as a platform for support and positive social interaction. In conclusion, the impact of social media on athletes’ mental health represents an evolving research field that requires broader global perspectives and multidisciplinary approaches to inform effective policies and interventions in the digital sports environment.